Outcomes of breast conserving therapy: Recurrence, imaging findings and histological correlation - Marara N. Sondezi; Ines Buccimazza; Ntombizakhona B. Madlala (South African Journal of Radiology, 2023)
Background: Breast conserving therapy (BCT) is the mainstay therapy in patients with early breast cancer and selected patients with locally advanced breast cancer. No formal audit has been performed on BCT at our institution.